Multi-objective stochastic programming energy management for integrated INVELOX turbines in microgrids: A new type of turbines - Shaterabadi, Mohammad; Jirdehi, Mehdi Ahmadi (Renewable energy, 2020)
In this paper, a new type of wind turbine that is called INVELOX has been used. INVELOX has many advantages such as six times more power generation than previous types, work at low speed, inconsiderable maintenance and investment costs, and reduce the environmental effects of previous wind turbines. Moreover, other renewable and nonrenewable generators are used in the energy management and scheduling of the microgrid. The test case is a microgrid with selling and buying energy capability in which the cost and pollution are considered as the objective functions. In the following, Uncertainties of wind speed, solar radiation and electrical-thermal loads are investigated and a multi-objective stochastic mixed integer linear programming is solved in the first scenario. Then, in the second scenario, the effects of fuel cost uncertainty on generation units and objective functions have been studied. The Epsilon constraints method and fuzzy satisfying are utilized to solve the problem and choose the best solution, respectively. By using of INVELOX turbines, total cost and pollution of the microgrid in both deterministic and stochastic planning are reduced from 192.68 $ to 97.23 $ and 249.28 $ to 126.38 $, as well 3334.76 Kg to 3302.7 and 3925.63 to 3910.2 Kg respectively. •Introducing INVELOX Turbine and considering different scenarios with/without it.•Multi-objective, deterministic and stochastic EM with uncertain parameters.•Using Epsilon constraints optimization method and fuzzy satisfying approach.•Considering Total cost and environmental pollution as objective functions.•Highly decreasing total cost and pollution with INVELOX Turbines.